The NLRP3 inflammasome in age-related cerebral small vessel disease manifestations: untying the innate immune response connection - Che Mohd Nassir, Che Mohd Nasril; Damodaran, Thenmoly; Ismail, Nurul Iman; Hashim, Sabarisah; Jaffer, Usman; Hamid, Hafizah Abdul; Mehat, Muhammad Zulfadli; Norazit, Anwar; Mustapha, Muzaimi (Multidisciplinary Digital Publishing Institute, 2023)
In this narrative review, we present the evidence on nucleotide-binding and oligomerization (NOD) domain-like receptor (NLR) family pyrin domain (PYD)-containing 3 (NLRP3) inflammasome activation for its putative roles in the elusive pathomechanism of aging-related cerebral small vessel disease (CSVD). Although NLRP3 inflammasome-interleukin (IL)-1β has been implicated in the pathophysiology of coronary artery disease, its roles in cerebral arteriothrombotic micro-circulation disease such as CSVD remains unexplored. Here, we elaborate on the current manifestations of CSVD and its’ complex pathogenesis and relate the array of activators and aberrant activation involving NLRP3 inflammasome with this condition. These neuroinflammatory insights would expand on our current understanding of CSVD clinical (and subclinical) heterogenous manifestations whilst highlighting plausible NLRP3-linked therapeutic targets.